2015
DOI: 10.1007/s10336-014-1101-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting leucocyte profiles in the little auk, a small Arctic seabird

Abstract: Leucocyte profiles, especially the heterophil/ lymphocyte ratio (H/L), are widely used to assess immune function and stress in birds. In this study, we investigated whether leucocyte profiles in a small colonial seabird, the little auk (Alle alle), are related to age (chicks, adults), sex or biometric traits, including body mass. We blood-sampled chicks at 4-8 and 14-18 days of life and chick-feeding adults with 14-20-and 24-30-day-old chicks. Relative numbers of heterophils and H/L generally differed among ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…Although we are aware of no previous research that examined relationships between plasma metabolite concentrations and H/L ratios in migrating birds, many studies have reported elevated H/L ratios in individuals with low body mass or experiencing food deprivation (Ots et al 2001;Gladbach et al 2010;Krams et al 2011;Jakubas et al 2015; but see Krams et al 2012). For example, male Upland Geese (Chloephaga picta leucoptera) showed negative correlation Table 1 Means ± standard error (SE) for condition indices and ratio of heterophils to lymphocytes (H/L ratio) in young (n = 282) and adult (n = 91) Common Snipe migrating through central Poland Because of the log-normal distribution, geometric mean ± SE is shown for the H/L ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Although we are aware of no previous research that examined relationships between plasma metabolite concentrations and H/L ratios in migrating birds, many studies have reported elevated H/L ratios in individuals with low body mass or experiencing food deprivation (Ots et al 2001;Gladbach et al 2010;Krams et al 2011;Jakubas et al 2015; but see Krams et al 2012). For example, male Upland Geese (Chloephaga picta leucoptera) showed negative correlation Table 1 Means ± standard error (SE) for condition indices and ratio of heterophils to lymphocytes (H/L ratio) in young (n = 282) and adult (n = 91) Common Snipe migrating through central Poland Because of the log-normal distribution, geometric mean ± SE is shown for the H/L ratio.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported for fish that production of ROS by phagocytic leukocytes is stimulated by prolactin (Yada et al 2001, Olavarría et al 2010. Given a five-fold higher level of prolactin during incubation compared to chick-rearing reported in the little auk (Wojczulanis- Jakubas et al 2015), this hormone may be responsible for stimulation of immune system during incubation, which in turns is reflected in higher OS and ROMs levels ( Fig. 1A-B).…”
Section: Discussionmentioning
confidence: 51%
“…We infer that snakes with higher growth, and a higher probability of recapture, are likely to have higher lifetime reproductive success ( = fitness, in evolutionary terms). To our knowledge, these are the first data to demonstrate empirical links between WBC counts and individual variation in life‐history traits in reptiles, though studies on birds have reported correlations between leuckocyte profiles of nestlings and fitness traits (Dehnhard et al., ; Jakubas, Wojczulanis‐Jakubas, & Kośmicka, ; Masello et al., ). Nonetheless, the causal basis of such links remains ambiguous.…”
Section: Discussionmentioning
confidence: 91%